Destruction of Carbon and Glass Fibers during Chip Machining of Composite Systems - Kroisová, Dora; Dvořáčková, Štěpánka; Knap, Artur; Knápek, Tomáš (Polymers, 2023)
Composite materials with carbon and glass fibers in an epoxy matrix are widely used systems due to their excellent mechanical parameters, and machining is a standard finishing operation in their manufacture. Previous studies focused exclusively on the characteristics of the fibers released into the air. This work aimed to analyze the nature of the material waste that remains on the work surface after machining. The dust on the work surface is made up of fibers and a polymer matrix, and due to its dimensions and chemical stability, it is a potentially dangerous inhalable material currently treated as regular waste. The smallest sizes of destroyed carbon fibers were generated during drilling and grinding (0.1 μm), and the smallest glass fiber particles were generated during milling (0.05 μm). Due to their nature, carbon fibers break by a tough fracture, and glass fibers by a brittle fracture. In both cases, the rupture of the fibers was perpendicular to or at an angle to the longitudinal axis of the fibers. The average lengths of destroyed carbon fibers from the tested processes ranged from 15 to 20 µm and 30 to 60 µm for glass fibers.
Keywords: carbon fibers; destruction; composite systems; glass fibers; machining